Continuous-time linear programming problems revisited: A perturbation approach - Wu, Hsien-Chung (Optimization, 2013)
The class of continuous-time linear programming problems under the assumption that the constraints are satisfied almost everywhere in the time interval [0, T] is taken into account in this article. Under this assumption, its corresponding discretized problems cannot be formulated by equally dividing the time interval [0, T] as subintervals of [0, T] . In this article, we also introduce the perturbed continuous-time linear programming problems to prove the strong duality theorem when the constraints are assumed to be satisfied a.e. in [0, T] .